2014
DOI: 10.1063/1.4896568
|View full text |Cite
|
Sign up to set email alerts
|

Crystal nucleation mechanism in melts of short polymer chains under quiescent conditions and under shear flow

Abstract: We present a molecular dynamics simulation study of crystal nucleation from undercooled melts of n-alkanes, and we identify the molecular mechanism of homogeneous crystal nucleation under quiescent conditions and under shear flow. We compare results for n-eicosane (C20) and npentacontahectane (C150), i.e., one system below the entanglement length and one above, at 20%-30% undercooling. Under quiescent conditions, we observe that entanglement does not have an effect on the nucleation mechanism. For both chain l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
85
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(102 citation statements)
references
References 80 publications
10
85
3
Order By: Relevance
“…When we advance from the supercooled melt towards the formation of the critical nucleus at t 0 , we observe first an increase in the global orientational order S 2 , then an increase in the radius of gyration of the segments, and finally the local density increases and the crystal structure is formed. The mechanism we observed here is the same as the one we have found in short polymer chains [30,58]. We conclude that, at 280 K the undercooling is so strong that nucleation is a local event which does not depend on the chain length.…”
Section: Nucleation Mechanismsupporting
confidence: 70%
See 2 more Smart Citations
“…When we advance from the supercooled melt towards the formation of the critical nucleus at t 0 , we observe first an increase in the global orientational order S 2 , then an increase in the radius of gyration of the segments, and finally the local density increases and the crystal structure is formed. The mechanism we observed here is the same as the one we have found in short polymer chains [30,58]. We conclude that, at 280 K the undercooling is so strong that nucleation is a local event which does not depend on the chain length.…”
Section: Nucleation Mechanismsupporting
confidence: 70%
“…We observe that nucleation is initiated by the alignment of the chain segments which participate in the formation of critical nucleus, similar to the mechanism previously observed for shorter chains [30,58]. During growth, the segments of the chains which are close to the growth front align with the long axis of the stems to attach to the cluster and then thicken by sliding/ slipping from the amorphous regions into the crystalline regions.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…We have traced this deviation in part to the overly large time step of 5 fs used in that work; such a large time step was reported by Waheed et al 37 to increase the chain relaxation time by only 10%, but its effect in suppressing nucleation is apparently more dramatic, compared to the more accurate rRESPA scheme used in this work. Our estimate for nucleation rate is also higher than the rate of 105 × 10 30 m −3 s −1 reported by Anwar et al at 250 K. 43 In this case, we suspect that the discrepancy is due to the application of the MFPT analysis method proposed by Wedekind et al 14 which employs the single-exponential approximation; as shown for our system in Table I, the singleexponential approximation results in an underestimation of the true nucleation rate. From the analysis herein, we conclude that the single exponential approximation should not hold for their conditions, given that their system is larger and the supercooling is deeper, both of which are expected to give rise to a greater degree of non-exponential behavior in the FPTD.…”
Section: Case Study: N-eicosane Nucleationcontrasting
confidence: 47%
“…At the molecular level, there have been simulation efforts using both Monte Carlo (MC) [13][14][15] and Molecular Dynamics (MD) [16][17][18][19][20][21] to study FIC; however, relatively few focused specifically on the kinetics of nucleation. 22 Given that nucleation is a transient event, a MC simulation cannot accurately capture its kinetics without an enormous amount of prior knowledge regarding the dynamic processes in the melt and their rates. For this reason, we believe that MD, which includes all of the classical physics of interacting particles, is the more attractive method for kinetic nucleation studies, where feasible, and directs readers to reviews that cover the application of MC methods to study FIC.…”
Section: Introductionmentioning
confidence: 99%